Ummah Business Market (UBM): Mosque-Based MSME Empowerment Application for Optimization of SDGs in the Time of Covid-19 - Eka Mega Pertiwi; Abu Dzarin Al Hamidy (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2021)
During the covid-19 pandemic, MSME business activities have decreased and have received small profits. Operations of mosques and amil institutions also experienced a decline. So, it needs an innovation that synergizes the community with MSMEs and mosques to increase the profits in economic and social activities that can encourage economic recovery. In this case, the mosque becomes the center of religious, economic, and social activities. The purpose of this study is to identify and produce a development model for the use of the Ummah Business Market (UBM) for mosque-based MSME empowerment applications and support post-Covid-19 economic recovery and poverty reduction as stated in the SDGs in goals 1 and 8. This study uses primary data with the type of action research that raises issues, makes solutions, and compiles a review of solutions from the Ummah Business Market (UBM) application process in empowering MSMEs during the pandemic. The results of this study indicate that the use and innovation of the mosque-based Ummah Business Market (UBM) application can increase operations and income for MSMEs and mosques, as well as create new jobs. In addition, able to optimize funds. Thus, benefits are obtained for economic recovery, poverty alleviation, and decent work. Ummah Business Market (UBM) also fosters a new attitude of society towards the economy and society, namely care, safe, and sharia.